Comparative Pharmacokinetics of Hydrophilic Components in Salvia miltiorrhiza Bge. and Carthamus tinctorius L. in Rats That Underwent Cerebral Ischemia Reperfusion Using an HPLC-DAD Method - Zhao, Xixi; Yu, Li; Chen, Yulin; Wang, Yu; Wan, Haitong; Yang, Jiehong (Frontiers in Pharmacology, 2020)
Background: In China, the combination of herb Salvia miltiorrhiza Bge. (Danshen) and Carthamus tinctorius L. (Honghua) is an effective treatment for stroke. A previous study showed that the combination of four herbal components: danshensu (DSS), hydroxysafflor yellow A (HSYA), salvianolic acid A (SAA), and salvianolic acid B (SAB) was effective for treatment of cerebral ischemia-reperfusion (I/R) injury in rats. However, the pharmacokinetic characteristics of this formula require further investigation. The present study investigated the pharmacokinetic differences between each component of the two formulas in cerebral I/R injury rats. Interactions between these components were analyzed. Methods: Focal cerebral I/R was induced by middle cerebral artery occlusion (MCAO). Rats that underwent MCAO were randomly divided into two groups and administered treatments through the tail vein. Blood samples were collected at predetermined time points following administration. The concentrations of DSS, HSYA, SAB, and SAA in rat plasma were determined using HPLC-DAD, and the main pharmacokinetic parameters were calculated. Pharmacokinetic parameters were calculated using DAS 3.2.6 software and SPSS 23.0 statistical analysis software. Results: Our results that DSS, HSYA, SAB and SAA in MCAO model rats interacted to alter pharmacokinetic parameters. For DSS and SAA, pharmacokinetic parameters with statistically significant differences including AUC(0-t), AUMC(0-t), MRT(0-t), VRT(0-t), t1/2z, Vz, CLz, Cmax (P <0.01). For HSYA, significant differences in the parameters including AUC(0-t), AUMC(0-t), MRT(0-t), VRT(0-t) (P <0.01), and CLz and Cmax (P <0.05). Conclusion: The difference in pharmacokinetic parameters in response to each component may have been due to differences in the dosages of the components (HSYA, SAA, SAB), metabolism by CYP450 enzymes, plasma protein binding rates, and effects related to the blood-brain barrier (BBB). Moreover, our study provided new insights, such as choosing appropriate dosages of active components of traditional Chinese medicine (TCM) to aid in prevention and treatment of cerebral ischemic diseases. The method and results in this study could provide a foundation for future pharmacological studies of the active components in Danshen and Honghua.